2017
DOI: 10.1037/dev0000384
|View full text |Cite
|
Sign up to set email alerts
|

Shape up: An eye-tracking study of preschoolers’ shape name processing and spatial development.

Abstract: Learning the names of geometric shapes is at the intersection of early spatial, mathematical, and language skills, all important for school-readiness and predictors of later abilities in science, technology, engineering, and mathematics (STEM). We investigated whether socioeconomic status (SES) influenced children’s processing of shape names and whether differences in processing were predictive of later spatial skills. 3-year-olds (N = 79) with mothers of varying education levels participated in an eye-trackin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 43 publications
(69 reference statements)
0
18
0
1
Order By: Relevance
“…That is, perhaps children who master spatial terms at a younger age have an advantage in spatial reasoning tasks over those who learn these terms later. Verdine et al (2017) found that speed at identifying shape terms at 3 years predicted later spatial skill, but did not predict concurrent spatial skill, lending support to this hypothesis. If dimensional adjective comprehension shows nonlinear growth, where children who learned the terms later could catch up to their early learning peers, we might be missing an effect of growth, seen by Pruden et al (2011).…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…That is, perhaps children who master spatial terms at a younger age have an advantage in spatial reasoning tasks over those who learn these terms later. Verdine et al (2017) found that speed at identifying shape terms at 3 years predicted later spatial skill, but did not predict concurrent spatial skill, lending support to this hypothesis. If dimensional adjective comprehension shows nonlinear growth, where children who learned the terms later could catch up to their early learning peers, we might be missing an effect of growth, seen by Pruden et al (2011).…”
Section: Discussionmentioning
confidence: 89%
“…In recent years interest has grown in the role of spatial language in early cognitive development (e.g., Bowerman & Choi, 2003;Ferrara et al, 2011;Pruden et al, 2011;Ratliff & Newcombe, 2008;Verdine et al, 2017). These studies look primarily at how a variety of spatial language word types influence thinking (e.g., size, location, shape terms).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations